2002
DOI: 10.1007/s11745-002-0881-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins: A potential tool for studying the role of glycerolipids in photosynthetic membranes

Abstract: A novel cyclodextrin derivative, i.e., permethylated-alpha-cyclodextrin (PM-alpha-CD), was used for removing glycerolipids from spinach thylakoid membranes and investigating their role in photosynthetic activities. A three-step selective removal of each lipid class was observed in treated membranes. Up to a concentration of 4 mM, PM-alpha-CD (in the presence of 75 microg chlorophyll a+b/mL), PM-alpha-CD displayed a marked selectivity for anionic lipids [sulfoquinovosyldiacylglycerol (SQDG) and phosphatidylglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the past few years, the cyclodextrins were applied successfully to the study of the photosynthetic activity in the thylakoid membrane of plant chloroplasts. It was shown that β-CD, a cyclodextrin containing seven d -glucose units, affects the spectroscopic characteristics and the electron transport properties of isolated thylakoid membranes. In short, β-CD induces a red-shift from 681 to 683 nm in the absorption and second derivative spectra of the thylakoids 7 which is assigned to perturbations affecting the Q Y (0,0) electronic transition in the plane of the chlorophyll (Chl) a molecule (see refs and ). However, the molecular interactions underlying this spectral shift are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the cyclodextrins were applied successfully to the study of the photosynthetic activity in the thylakoid membrane of plant chloroplasts. It was shown that β-CD, a cyclodextrin containing seven d -glucose units, affects the spectroscopic characteristics and the electron transport properties of isolated thylakoid membranes. In short, β-CD induces a red-shift from 681 to 683 nm in the absorption and second derivative spectra of the thylakoids 7 which is assigned to perturbations affecting the Q Y (0,0) electronic transition in the plane of the chlorophyll (Chl) a molecule (see refs and ). However, the molecular interactions underlying this spectral shift are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…CDs are also able to bind phospholipids (Ohtani et al, 1989;Puglisi et al, 1996;Rawyler and Siegenthaler, 1996;Fauvelle et al, 1997;Debouzy et al, 1998;Nishijo and Mizuno, 1998;Nishijo et al, 2000;Leventis and Silvius, 2001;Duchêne and Siegenthaler, 2002;Anderson et al, 2004;Giocondi et al, 2004;Hatzi et al, 2007;Piel et al, 2007;Kainu et al, 2010;Huang and London, 2013). This interaction has a different CD-specificity compared with that observed for sterols.…”
Section: Introductionmentioning
confidence: 96%